Shear bond strength of oil well cement in carbonic acid environment. (October 2018) - Hwang, Jueun; Ahmed, Ramadan; Tale, Sagar; Shah, Subhash
Highlights: Shear Bond Strength (SBS) is an essential property of oil well cement. This is an experimental study on the effect of carbonation on the SBS of cement. Specimens were aged for 14 days in an autoclave, and their properties were measured. Temperature has a prominent effect on the carbonation of cement. SBS increased with the carbonation. Abstract: Shear Bond Strength (SBS) is an important property of cement that determines the life of oil and gas wells. This paper presents the results of an experimental study on the effect of carbonation on the SBS of cement under high-pressure high-temperature (HPHT) condition. The study is aimed at examining the effects of CO2 concentration, temperature, and pressure on SBS of cement containing 35% of silica flour. The study was conducted by aging two types of specimens (i.e. cement cores and SBS samples made of steel pipe and cement). After curing, the specimens were aged for 14 days in an autoclave. The autoclave was 80% filled with brine saturated with mixed gas containing CO2 and CH4 . Aging pressure (21–62 MPa), temperature (38–221 °C) and CO2 concentration (10–100% CO2 ) were varied. After aging, the specimens were recovered, and their SBS, porosity and mineralogical composition were determined to assess the level of carbonation and degradation. To identify the most dominant factor affecting the SBS of cement, measurements were analyzed applying the Analysis of Variance (ANOVA) method. The analysis showed that temperature has a more prominent effect on the carbonation process than pressure and CO2 concentration. Furthermore, results showed strong interaction effect among the main influential factors (pressure, temperature and CO2 concentration). SBS increased with the carbonation. Medium-range temperatures (107 and 177 °C) caused high levels of carbonation as manifested by huge improvement in SBS and a significant reduction in porosity after exposure to a carbonic acid environment.